Pengaruh Shopping Lifestyle, Hedonic Shopping Value, dan Shopping Emotion Terhadap Impulse Buying Pada Konsumen Shopee (Studi pada Masyarakat di Ponorogo) - Dyah Ayu Widyawati; Siti Chamidah; Sri Hartono (Jurnal Manajemen, 2023)
This study aims to determine the effect of Shopping Lifestyle, Hedonic Shopping Value, and Shopping Emotion on Impulse Buying of Shopee Consumers (study of the community in Ponorogo). The analytical technique used in this research is quantitative analysis technique using SPSS version 16 statistical program. This study involved 100 people ini Ponorogo as respondents. The result particially show that Shopping Lifestyle has a positive and significant effect on Impulse Buying, Hedonic Shopping Value has a positive and significant effect on Impulse Buying, and Shopping Emotion has a significant and negative effect on Impulse Buying. While the result of study simultaneously show that three independent variable have a positive and significant effect on Impulse Buying.